Protection coordination issues with double-fed induction generator wind generation on small islanded networks - Rossi, R.; Masoum, Mohammad Sherkat (Engineers Media Pty, 2014)
The application of wind generation system is widely used for interconnecting to both solid redundant and isolated weak networks. However, the application of wind generation systems to islanded power networks with large industrial loads has not been subject to extensive research. This paper reviews issues associated with protection coordination requirements as applied to double-fed induction generator wind generation systems interfaced to islanded power networks that are specifically applied to industrial environments in remote operations. The use of a new protection approach to such installations is considered and a solution proposed, specifically, when the wind generation bus bars and high voltage cables are under faulted conditions. The use of directional protection relays can assist with general coordination, critical fault clearing time requirements, some ride-through capabilities and selective tripping.